Optical film with surface protective film and inspection method for optical film
The optical film with a surface protection film layer, where the release forces of the innermost and outermost films are optimized, addresses the need for precise defect inspection while maintaining protection, specifically for VR goggles.
Patent Information
- Application Number
- JP2023152010
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
AI Technical Summary
The challenge is to develop an optical film with a surface protection film that can be inspected for defects while remaining protected, particularly for VR goggles where stricter defect management is required.
The optical film is designed with a surface protection film layer comprising two or more surface protection films. The release forces of the innermost and outermost surface protection films are adjusted to satisfy specific relationships, preventing simultaneous peeling during inspection. This allows for precise defect inspection while maintaining protection.
The solution effectively prevents the innermost surface protection film from peeling off simultaneously with the outermost film, enabling accurate defect inspection without surface contamination, thus ensuring reliable performance in VR applications.
Smart Images

Figure 2025044443000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical film with a surface protective film and an inspection method for the optical film. [Background technology]
[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices), are rapidly becoming widespread. In image display devices, optical members such as polarizing members and phase difference members are generally used to realize image display and to improve the performance of the image display (see, for example, Patent Document 1).
[0003] In recent years, new applications for image display devices have been developed. For example, goggles with displays (VR goggles) for realizing virtual reality (VR) have begun to be commercialized. In VR goggles, the image displayed on the display panel is enlarged for viewing by the viewer, so the optical films used in VR goggles require stricter defect management than the optical films used in conventional image display devices. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2021-103286 A Summary of the Invention [Problem to be solved by the invention]
[0005] As described above, strict defect management is required for optical films applied to VR goggles, and therefore precise defect inspection may be performed by automated optical inspection (AOI). On the other hand, it is preferable that the surface of the optical film is protected until it is subjected to the final assembly process. Therefore, the main object of the present invention is to provide an optical film with a surface protective film that can be suitably inspected for defects while being protected by the surface protective film. [Means for solving the problem]
[0006] [1] According to one aspect of the present invention, there is provided an optical film with a surface protective film, comprising an optical film and a surface protective film layer arranged on one side of the optical film, wherein the surface protective film layer includes two or more surface protective films having a substrate and a pressure-sensitive adhesive layer, and a peel force P1 of an innermost surface protective film arranged closest to the optical film of the surface protective film layer, and a peel force P2 of an outermost surface protective film arranged on the outermost side of the surface protective film layer, from the optical film, satisfy the relationship of the following formula (1): P2≦3.5×P1. [2] In the optical film with a surface protective film described in [1] above, the surface protective film layer may be composed of the innermost surface protective film, an intermediate surface protective film, and the outermost surface protective film, and the peeling force P2 of the outermost surface protective film to the intermediate surface protective film and the peeling force P3 of the intermediate surface protective film to the innermost surface protective film may satisfy the relationship of formula (2): P2≦2.5×P3 and formula (3): P3≦2×P1. [3] In the optical film with a surface protective film according to the above [1] or [2], the ratio (T1 / T2) of the thickness T1 of the innermost surface protective film to the thickness T2 of the outermost surface protective film may be 1.03 or more. [4] In the optical film with a surface protective film according to any one of [1] to [3] above, the bending strength of the substrate of the innermost surface protective film at 23°C may be equal to or greater than the bending strength of the substrate of the outermost surface protective film at 23°C. [5] In the optical film with a surface protective film according to any one of [1] to [4] above, the surface of the optical film facing the surface protective film layer may be an antireflection layer. [6] In the optical film with a surface protective film according to any one of [1] to [5] above, the water contact angle of the surface of the optical film on the side of the surface protective film layer may be 80° or more. [7] According to another aspect of the present invention, there is provided a method for inspecting an optical film, the method including peeling off the outermost surface protective film from an optical film with a surface protective film described in any one of [1] to [6] above to obtain the optical film protected by at least the innermost surface protective film, and subjecting the optical film protected by at least the innermost surface protective film to defect inspection. Effect of the Invention
[0007] According to an embodiment of the present invention, a surface protective film layer including two or more surface protective films is disposed on one side of an optical film, and the peeling force of the innermost surface protective film from the optical film and the peeling force of the outermost surface protective film from the adjacent surface protective film are adjusted to satisfy a predetermined relationship, thereby making it possible to suppress simultaneous peeling of the innermost surface protective film when peeling off the outermost surface protective film. With such an optical film with a surface protective film, by peeling off the outermost surface protective film, it is possible to suitably obtain an optical film in a state protected by a surface protective film located inside and prevented from adhesion of scratches, dirt, etc. Even if an optical film in a state protected by such a clean surface protective film is subjected to a defect inspection as it is, erroneous detection of defects caused by the surface protective film can be suppressed. [Brief description of the drawings]
[0008] [Figure 1] 1 is a schematic diagram showing a general configuration of an example of a display system to which an optical film with a surface protective film according to an embodiment of the present invention can be applied. [Diagram 2] 1 is a schematic cross-sectional view showing an outline of a configuration of an optical film with a surface protective film according to one embodiment of the present invention. [Diagram 3] 1 is a schematic cross-sectional view showing an outline of a configuration of an optical film with a surface protective film according to one embodiment of the present invention. [Figure 4] FIG. 2 is a schematic cross-sectional view illustrating an example of a configuration of an optical film applicable to the optical film with a surface protective film according to an embodiment of the present invention. [Diagram 5] FIG. 2 is a schematic cross-sectional view illustrating an example of a configuration of an optical film applicable to the optical film with a surface protective film according to an embodiment of the present invention. [Figure 6A] FIG. 2 is a schematic plan view illustrating a method for measuring the peel strength of a surface protective film. [Figure 6B] FIG. 2 is a schematic side view illustrating a method for measuring the peel strength of a surface protective film. [Figure 7A] FIG. 2 is a schematic plan view illustrating a peel test method. [Figure 7B] FIG. 2 is a schematic plan view illustrating a peel test method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, the embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to these embodiments. In order to clarify the description, the drawings may show the width, thickness, shape, etc. of each part more diagrammatically than the embodiments, but these are merely examples and do not limit the interpretation of the present invention.
[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When an angle is mentioned in this specification, unless otherwise specified, the angle includes both clockwise (+) and counterclockwise (-) angles with respect to a reference direction. Thus, for example, "45°" means ±45°. Also, in this specification, "substantially parallel" includes a range of 0°±10°, preferably within a range of 0°±5°. "Substantially perpendicular" includes a range of 90°±10°, preferably within a range of 90°±5°.
[0011] A. Display System FIG. 1 is a schematic diagram showing an outline of an example of a display system to which the optical film with a surface protective film according to an embodiment of the present invention can be applied. FIG. 1 shows the arrangement and shape of each component of a display system 2. The display system 2 includes a display element 12, a reflecting section 14 including a reflective polarizing member, a first lens section 16, a half mirror 18, a first phase difference member 20, a second phase difference member 22, and a second lens section 24. The reflecting section 14 is disposed in front of the display surface 12a of the display element 12, and can reflect light emitted from the display element 12. The first lens section 16 is disposed on the optical path between the display element 12 and the reflecting section 14, and the half mirror 18 is disposed between the display element 12 and the first lens section 16. The first phase difference member 20 is disposed on the optical path between the display element 12 and the half mirror 18, and the second phase difference member 22 is disposed on the optical path between the half mirror 18 and the reflecting section 14.
[0012] The display element 12 is, for example, a liquid crystal display or an organic EL display, and has a display surface 12a for displaying an image. The light emitted from the display surface 12a passes through, for example, a polarizing member (typically, a polarizing film) that may be included in the display element 12, and is converted into a first linearly polarized light.
[0013] The first phase difference member 20 includes a first λ / 4 member that can convert a first linearly polarized light incident on the first phase difference member 20 into a first circularly polarized light. When the first phase difference member does not include a member other than the first λ / 4 member, the first phase difference member may correspond to the first λ / 4 member. The first phase difference member 20 may be provided integrally with the display element 12.
[0014] The half mirror 18 transmits the light emitted from the display element 12 and reflects the light reflected by the reflecting portion 14 toward the reflecting portion 14. The half mirror 18 is provided integrally with the first lens portion 16.
[0015] The second phase difference member 22 includes a second λ / 4 member that can transmit light reflected by the reflecting section 14 and the half mirror 18 through the reflecting section 14. When the second phase difference member does not include any member other than the second λ / 4 member, the second phase difference member may correspond to the second λ / 4 member. The second phase difference member 22 may be provided integrally with the first lens section 16.
[0016] The first circularly polarized light output from the first λ / 4 member included in the first phase difference member 20 passes through the half mirror 18 and the first lens unit 16, and is converted into the second linearly polarized light by the second λ / 4 member included in the second phase difference member 22. The second linearly polarized light output from the second λ / 4 member is reflected toward the half mirror 18 without passing through the reflective polarizing member included in the reflecting unit 14. At this time, the polarization direction of the second linearly polarized light incident on the reflective polarizing member included in the reflecting unit 14 is the same as the reflection axis of the reflective polarizing member. Therefore, the second linearly polarized light incident on the reflecting unit is reflected by the reflective polarizing member.
[0017] The second linearly polarized light reflected by the reflecting unit 14 is converted into the second circularly polarized light by the second λ / 4 member included in the second phase difference member 22, and the second circularly polarized light output from the second λ / 4 member passes through the first lens unit 16 and is reflected by the half mirror 18. The second circularly polarized light reflected by the half mirror 18 passes through the first lens unit 16 and is converted into the third linearly polarized light by the second λ / 4 member included in the second phase difference member 22. The third linearly polarized light passes through the reflective polarizing member. At this time, the polarization direction of the third linearly polarized light incident on the reflective polarizing member included in the reflecting unit 14 is the same as the transmission axis of the reflective polarizing member. Therefore, the third linearly polarized light incident on the reflecting unit 14 passes through the reflective polarizing member.
[0018] The light transmitted through the reflecting portion 14 passes through the second lens portion 24 and enters the user's eye 26.
[0019] The display system 2 may include an absorptive polarizing member (typically, an absorptive polarizing film) in front of the reflective polarizing member in the reflector 14. The reflection axis of the reflective polarizing member and the absorption axis of the absorptive polarizing member may be arranged substantially parallel to each other, and the transmission axis of the reflective polarizing member and the transmission axis of the absorptive polarizing member may be arranged substantially parallel to each other. This allows the third linearly polarized light that has passed through the reflective polarizing member to pass through the absorptive polarizing member as it is.
[0020] For example, the absorption axis of the polarizing member that may be included in the display element 12 and the reflection axis of the reflective polarizing member that may be included in the reflecting section 14 may be disposed approximately parallel to each other or approximately perpendicular to each other. The angle between the absorption axis of the polarizing member that may be included in the display element 12 and the slow axis of the first λ / 4 member that is included in the first phase difference member 20 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°. The angle between the absorption axis of the polarizing member that may be included in the display element 12 and the slow axis of the second λ / 4 member that is included in the second phase difference member 22 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°.
[0021] The in-plane retardation Re(550) of the first λ / 4 member is, for example, 100 nm to 190 nm, and may be 110 nm to 180 nm, 130 nm to 160 nm, or 135 nm to 155 nm. The first λ / 4 member preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. The Re(450) / Re(550) of the first λ / 4 member may be, for example, 0.75 or more and less than 1, or 0.8 or more and 0.95 or less.
[0022] The in-plane retardation Re(550) of the second λ / 4 member is, for example, 100 nm to 190 nm, and may be 110 nm to 180 nm, 130 nm to 160 nm, or 135 nm to 155 nm. The second λ / 4 member preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. The Re(450) / Re(550) of the second λ / 4 member may be, for example, 0.75 or more and less than 1, or 0.8 or more and 0.95 or less.
[0023] As described above, in the display system 2, the light representing an image emitted forward from the display surface 12a of the display element 12 is magnified by the first lens section and the second lens section, and can be viewed by a viewer. The optical film used in such a display system requires stricter defect management than that of conventional image display devices. For example, the defect size allowed for the optical film used in the above display system can be, for example, 80 μm or less, 50 μm or less, or 30 μm or less, and can be, for example, 5 μm or more, or 10 μm or more.
[0024] B. Optical film with surface protection film The optical film with a surface protective film according to the embodiment of the present invention includes an optical film and a surface protective film layer disposed on one side of the optical film. The surface protective film layer includes two or more surface protective films (hereinafter, sometimes referred to as "PFs") having a substrate and a pressure-sensitive adhesive layer. Typically, a peeling force P1 of a PF (hereinafter, sometimes referred to as "innermost layer PF") disposed on the innermost side (closest to the optical film side) of the surface protective film layer against the optical film, and a peeling force P2 of a PF (hereinafter, sometimes referred to as "outermost layer PF") disposed on the outermost side (opposite the optical film side) of the surface protective film layer against an adjacent PF satisfy the relationship of the following formula (1). P1 and P2 preferably satisfy the relationship of the following formula (1a) or (1b). In addition, P1 and P2 may satisfy the relationship of the following formula (1c) or (1d). When P1 and P2 satisfy such a relationship, simultaneous peeling of the innermost layer PF when peeling the outermost layer PF can be suitably suppressed. P2≦3.5×P1 (1) P2≦3×P1 (1a) P2≦2.5×P1 (1b) P2 ≧ 0.9 × P1 (1c) P2 ≧ 1 × P1 (1d)
[0025] FIG. 2 is a schematic cross-sectional view showing a schematic configuration of an optical film with a surface protective film according to one embodiment of the present invention. The optical film with a surface protective film 100A includes an optical film 50 and a surface protective film layer 60 arranged on one side of the optical film 50. The surface protective film layer 60 is composed of an innermost layer PF62 arranged on the innermost side and an outermost layer PF64 arranged on the outermost side. The innermost layer PF62 and the outermost layer PF64 have substrates 62a and 64a and adhesive layers 62b and 64b, respectively. In the optical film with a surface protective film 100A, the innermost layer PF62 is the PF adjacent to the outermost layer PF64, and the peel force of the outermost layer PF64 against the innermost layer PF62 is a peel force P2. The peel force of the innermost layer PF62 against the optical film 50 is a peel force P1.
[0026] FIG. 3 is a schematic cross-sectional view showing a schematic configuration of an optical film with a surface protective film according to another embodiment of the present invention. The optical film with a surface protective film 100B includes an optical film 50 and a surface protective film layer 60 arranged on one side of the optical film 50. The surface protective film layer 60 is composed of an innermost layer PF62 arranged on the innermost side, an outermost layer PF64 arranged on the outermost side, and an intermediate PF66 arranged therebetween. The intermediate PF66 has a base material 66a and a pressure-sensitive adhesive layer 66b. Typically, the peel force P1 of the innermost layer PF62 to the optical film 50 and the peel force P2 of the outermost layer PF64 to the intermediate PF66 satisfy the relationship of the above formula (1). P1 and P2 preferably satisfy the relationship of the above formula (1a) or (1b). In addition, P1 and P2 may satisfy the relationship of the above formula (1c) or (1d). Furthermore, the peel forces P3 and P2 of the intermediate PF 66 from the innermost PF 62 preferably satisfy the relationship of the following formula (2), and more preferably satisfy the relationship of the following formula (2a) and / or (2b). P3 and P1 may preferably satisfy the relationship of the following formula (3), and more preferably satisfy the relationship of the following formula (3a) and / or (3b). When P1 to P3 satisfy such relationships, in addition to the simultaneous peeling of the innermost PF and / or intermediate PF when peeling the outermost PF, simultaneous peeling of the innermost PF when peeling the intermediate PF can be suitably suppressed. P2≦2.5×P3 (2) P2≦2.3×P3 (2a) P2 ≧ 2 × P3 (2b) P3≦2×P1 (3) P3≦1.5×P1 (3a) P3≧0.9×P1 (3b)
[0027] The peeling force P1 of the innermost layer PF to the optical film may be, for example, 0.06 N / 25 mm or less, 0.055 N / 25 mm or less, or 0.05 N / 25 mm or less. The peeling force P1 may be, for example, 0.02 N / 25 mm or more, 0.025 N / 25 mm or more, or 0.03 N / 25 mm or more.
[0028] The peeling force P2 of the outermost layer PF with respect to the adjacent PF can be set to satisfy the above formula (1), preferably at least one of (1a) to (1d). The peeling force P2 may be, for example, 0.21 N / 25 mm or less, 0.18 N / 25 mm or less, or 0.15 N / 25 mm or less. The peeling force P2 may be, for example, 0.018 N / 25 mm or more, 0.02 N / 25 mm or more, or 0.022 N / 25 mm or more.
[0029] The peeling force P3 of the intermediate PF to the innermost layer PF can be set to satisfy, for example, the above formula (2) and / or (3), preferably (2a), (2b), (3a), and / or (3b). The peeling force P3 may be, for example, 0.12 N / 25 mm or less, 0.11 N / 25 mm or less, or 0.09 N / 25 mm or less. The peeling force P3 may be, for example, 0.007 N / 25 mm or more, 0.008 N / 25 mm or more, or 0.018 N / 25 mm or more.
[0030] The peel strengths P1 to P3 were measured under conditions of 23° C. and 50% RH at a peel angle of 180° and a peel speed of 300 mm / min.
[0031] [Surface protection film layer] The surface protection film layer includes two or more PFs. The number of PFs included in the surface protection film layer can be selected according to the purpose, and is preferably 2 or 3. For example, in the embodiment shown in FIG. 2, the surface protection film layer 60 is composed of an innermost layer PF62 and an outermost layer PF64, and includes two PFs. Also, for example, in the embodiment shown in FIG. 3, the surface protection film layer 60 is composed of an innermost layer PF62, an intermediate PF66, and an outermost layer PF64, and includes three PFs. Each PF has a base material and a pressure-sensitive adhesive layer provided on one side thereof, and can be attached to an adjacent member by the pressure-sensitive adhesive layer. The PF is a process member that is temporarily attached (temporarily attached) to the optical film, and is peeled off and removed when the optical film is used.
[0032] The haze of each of the PFs included in the surface protective film layer is, for example, 10% or less, preferably 5% or less, more preferably 4% or less, and even more preferably 3% or less, and typically 0.05% or more. In particular, the haze of the PFs (e.g., the innermost PF, the intermediate PF) disposed inside the outermost PF is preferably low, and may be, for example, 5% or less. When the haze of the PF disposed inside the outermost PF is low, the optical film can be subjected to precise defect inspection while being protected by the PF.
[0033] The total light transmittance of each of the PFs included in the surface protective film layer is, for example, 80% or more, preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more. In particular, the total light transmittance of the PF (e.g., the innermost layer PF, the intermediate PF) disposed inside the outermost layer PF is preferably high, and may be, for example, 85% or more. When the total light transmittance of the PF disposed inside the outermost layer PF is high, the optical film can be subjected to precise defect inspection while being protected by the PF.
[0034] The thickness of each of the PFs contained in the surface protective film layer is, for example, 15 μm to 250 μm, preferably 30 μm to 150 μm, and more preferably 40 μm to 100 μm.
[0035] In one embodiment, the ratio (T1 / T2) of the thickness T1 of the innermost layer PF to the thickness T2 of the outermost layer PF may be 1.03 or more, for example, 1.03 to 1.2 or 1.2 to 1.5. When the ratio (T1 / T2) is within the above range, simultaneous peeling of the innermost layer PF when peeling off the outermost layer PF can be suitably suppressed.
[0036] Any suitable resin film may be selected as the substrate constituting the PF. Specific examples of materials that are the main components of the resin film include transparent resins such as cycloolefin (COP)-based resins such as polynorbornene-based resins, polyester-based resins such as polyethylene terephthalate (PET), cellulose-based resins such as triacetyl cellulose (TAC), polycarbonate (PC), (meth)acrylic resins, polyvinyl alcohol-based resins, polyamide-based resins, polyimide-based resins, polyethersulfone-based resins, polysulfone-based resins, polystyrene-based resins, polyolefin-based resins, and acetate-based resins. In addition, examples of the resins include thermosetting resins or ultraviolet-curing resins such as (meth)acrylic resins, urethane-based resins, (meth)acrylic urethane-based resins, epoxy-based resins, and silicone-based resins. The term "(meth)acrylic resin" refers to acrylic resins and / or methacrylic resins. In addition, examples of the resins include glassy polymers such as siloxane-based polymers. In addition, the polymer films described in JP 2001-343529 A (WO01 / 37007) can also be used. The material of this film can be, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain, such as a resin composition having an alternating copolymer of isobutene and N-methylmaleimide and an acrylonitrile-styrene copolymer. The polymer film can be, for example, an extrusion molded product of the above resin composition. The materials of the resin film can be used alone or in combination.
[0037] The substrate preferably contains at least one transparent resin selected from the group consisting of COP, PET, TAC, PC and (meth)acrylic, more preferably contains at least one transparent resin selected from the group consisting of COP, PET, PC and (meth)acrylic, and even more preferably contains at least one transparent resin selected from the group consisting of COP, PET and PC. When the substrate contains the transparent resin, false detections due to PF in defect inspection can be more stably reduced.
[0038] The substrate may contain an antioxidant, an ultraviolet absorber, a light stabilizer, a nucleating agent, a filler, a pigment, a surfactant, an antistatic agent, etc. The surface of the substrate (the surface opposite to the pressure-sensitive adhesive layer) may be provided with an easy-adhesion layer, an easy-slip layer, an antiblocking layer, an antistatic layer, an antireflection layer, an oligomer prevention layer, etc.
[0039] The above substrate has a bending strength of, for example, 40 MPa to 200 MPa, preferably 50 MPa to 180 MPa, and more preferably 60 MPa to 150 MPa at 23° C. The bending strength can be measured, for example, by a method in accordance with ISO178·JIS K7171.
[0040] The ratio (E1 / E2) of the bending strength E1 of the substrate constituting the innermost layer PF to the bending strength E2 of the substrate constituting the outermost layer PF is, for example, 1 or more, preferably 1.1 to 1.4, and may be, for example, 1.1 to 1.2 or 1.2 to 1.4. The ratio (E1 / E3) of the bending strength E1 of the substrate constituting the innermost layer PF to the bending strength E3 of the substrate constituting the intermediate PF is, for example, 1 or more, preferably 1 to 1.17, and may be, for example, 1 to 1.05, 1.05 to 1.09, or 1.09 to 1.17. The ratio (E3 / E2) of the bending strength E3 of the substrate constituting the intermediate PF to the bending strength E2 of the substrate constituting the outermost layer PF is, for example, 1 or more, preferably 1.1 to 1.4, and may be, for example, 1.1 to 1.2 or 1.2 to 1.4. When the substrate of the PF to be peeled off has flexibility equal to or greater than that of the substrate of the remaining PF, simultaneous peeling can be suitably suppressed.
[0041] The thickness of the substrate is typically 5 μm or more, preferably 20 μm or more, and typically 100 μm or less, preferably 80 μm or less.
[0042] The adhesive layer constituting the PF may be composed of any suitable adhesive. The adhesive constituting the adhesive layer typically contains at least one adhesive selected from the group consisting of (meth)acrylic adhesives, urethane adhesives, and silicone adhesives. Preferably, the adhesive layer contains a (meth)acrylic adhesive.
[0043] The (meth)acrylic adhesive contains a polymer (hereinafter referred to as a (meth)acrylic polymer) of a monomer component mainly composed of alkyl (meth)acrylate. In other words, the (meth)acrylic polymer contains a structural unit derived from alkyl (meth)acrylate. The content ratio of the structural unit derived from alkyl (meth)acrylate in the (meth)acrylic polymer is typically 50% by weight or more, preferably 80% by weight or more, more preferably 93% by weight or more, and for example 100% by weight or less, preferably 98% by weight or less.
[0044] The alkyl group of the alkyl (meth)acrylate may be linear or branched. The number of carbon atoms of the alkyl group is, for example, 1 or more and 18 or less. Examples of the alkyl group include a methyl group, an ethyl group, a butyl group, a 2-ethylhexyl group, a decyl group, an isodecyl group, and an octadecyl group. The alkyl (meth)acrylate may be used alone or in combination. The average number of carbon atoms of the alkyl group is preferably 3 to 10.
[0045] The (meth)acrylic polymer may contain a structural unit derived from a copolymerizable monomer polymerizable with the alkyl (meth)acrylate, in addition to the structural unit derived from the alkyl (meth)acrylate. Examples of the copolymerizable monomer include a carboxyl group-containing monomer and a hydroxyl group-containing monomer. The copolymerizable monomer may be used alone or in combination.
[0046] The carboxyl group-containing monomer is a compound that contains a carboxyl group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the carboxyl group-containing monomer include (meth)acrylic acid, carboxyethyl (meth)acrylate, maleic acid, fumaric acid, and crotonic acid, and preferably (meth)acrylic acid. When the (meth)acrylic polymer contains a structural unit derived from a carboxyl group-containing monomer, the adhesive properties of the pressure-sensitive adhesive layer can be improved. When the (meth)acrylic polymer contains a structural unit derived from a carboxyl group-containing monomer, the content of the structural unit derived from the carboxyl group-containing monomer is preferably 0.01% by weight or more and 10% by weight or less.
[0047] The hydroxyl group-containing monomer is a compound that contains a hydroxyl group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)-methyl acrylate, preferably 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate, and more preferably 2-hydroxyethyl (meth)acrylate. When the (meth)acrylic polymer contains a structural unit derived from a hydroxyl group-containing monomer, the durability of the adhesive layer can be improved. When the (meth)acrylic polymer contains a structural unit derived from a hydroxyl group-containing monomer, the content ratio of the structural unit derived from the hydroxyl group-containing monomer in the (meth)acrylic polymer is preferably 0.01% by weight or more and 10% by weight or less.
[0048] The weight average molecular weight Mw of the (meth)acrylic polymer is, for example, 100,000 to 2,000,000, and preferably 200,000 to 1,000,000.
[0049] The (meth)acrylic adhesive may contain a crosslinking agent. Representative examples of the crosslinking agent include organic crosslinking agents and polyfunctional metal chelates, and preferably organic crosslinking agents. Examples of the organic crosslinking agent include isocyanate crosslinking agents, peroxide crosslinking agents, epoxy crosslinking agents, and imine crosslinking agents, and more preferably isocyanate crosslinking agents. When the adhesive contains a crosslinking agent, the content of the crosslinking agent is usually 0.01 parts by weight or more and 15 parts by weight or less with respect to 100 parts by weight of the (meth)acrylic polymer.
[0050] The above-mentioned adhesives ((meth)acrylic adhesives, urethane adhesives and silicone adhesives) may contain various additives in appropriate proportions as necessary. By adjusting the composition of the base polymer (e.g., the type and content of monomers, the type and content of crosslinking agent, etc.), the molecular weight of the base polymer, the type or content of additives, etc., a pressure-sensitive adhesive layer having the desired adhesiveness to the adherend can be obtained.
[0051] Examples of the additives include a polymerization initiator, a solvent, a polymerization catalyst, a crosslinking catalyst, a silane coupling agent, a tackifier, a plasticizer, a softener, an antidegradant, a filler, a colorant (pigment, dye, etc.), a light stabilizer, an ultraviolet absorber, an antioxidant, a surfactant, an antistatic agent, and a chain transfer agent.
[0052] The thickness of the pressure-sensitive adhesive layer is, for example, 10 μm or more, preferably 12 μm or more, and for example, 40 μm or less, preferably 30 μm or less, more preferably 25 μm or less.
[0053] The adhesive layer may be formed on the surface of the substrate by direct writing or by transfer. In the case of direct writing, the adhesive is directly applied to the surface of the substrate to form the adhesive layer. In the case of transfer, the adhesive is applied to the surface of the release liner to form the adhesive layer, and then the substrate is attached to the adhesive layer. In particular, when the substrate contains an amorphous resin having a relatively low glass transition temperature Tg (for example, 150 °C or lower), the adhesive layer is preferably formed by a transfer process. In the case of a transfer process, it is possible to suppress the high temperature during drying required for the formation of the adhesive layer from affecting the substrate.
[0054] [Optical film] The optical film can have any suitable configuration according to the purpose, application, etc. The optical film may have a single-layer structure or may be a laminate having a multilayer structure. For example, the optical film can be a laminate having an antireflection layer as one of the outermost layers. For a layer with a small surface free energy such as an antireflection layer, it is difficult for the PF to exhibit sufficient adhesive force, and as a result, there may be a case where P1 cannot be made sufficiently large (for example, when P1 < P2). Even in such a case, according to the embodiment of the present invention, since the peeling force between the outer PF and the inner PF is adjusted to a predetermined relationship, it is possible to preferably suppress the inner PF from peeling off simultaneously when the outer PF peels off.
[0055] In one embodiment, the water contact angle of the surface of the optical film on the side of the surface protection film layer is, for example, 80° or more, and may be 90° or more or 100° or more. The water contact angle can be, for example, 150° or less, or for example, 140° or less. When the wettability of the surface of the optical film on the side of the surface protection film layer is low, the effects of the present invention can be more preferably obtained.
[0056] FIG. 4 is a schematic cross-sectional view for explaining an example of the configuration of an optical film applicable to an embodiment of the present invention. The optical film 50a includes a pressure-sensitive adhesive layer 31, a polarizing member 10, a first phase difference member 20, and a first protective member 41 in this order. The polarizing member 10, the first phase difference member 20, and the first protective member 41 are laminated via adhesive layers 33 and 34. The adhesive layers 33 and 34 are typically adhesive layers or pressure-sensitive adhesive layers, and are preferably pressure-sensitive adhesive layers. The adhesive layers 33 and 34 have a thickness of, for example, 0.05 μm to 30 μm. The surface of the pressure-sensitive adhesive layer 31 is protected by a release liner 36 until it is used. With respect to the optical film 50a, a surface protection film layer is disposed on the surface on the first protective member 41 side.
[0057] The optical film 50a can be suitably used in the display system 2 exemplified in Fig. 1. Specifically, the polarizing member 10 in the optical film 50a is a polarizing member that can be included in the display element 12, and a display system in which the first retardation member 20 is provided integrally with the display element 12 can be manufactured by peeling the release liner 36 from the optical film 50a and bonding it to a component of the display element 12 via the exposed pressure-sensitive adhesive layer 31.
[0058] In the example shown in FIG. 4, the first phase difference member 20 includes, in addition to the first λ / 4 member 20a, a member (so-called positive C plate) 20b whose refractive index characteristics can show the relationship of nz>nx=ny. The first phase difference member 20 has a laminated structure of the first λ / 4 member 20a and the first positive C plate 20b. Unlike the illustrated example, the first positive C plate 20b may be located closer to the polarizing member 10 than the first λ / 4 member 20a, and the first positive C plate 20b may be omitted. The first λ / 4 member 20a and the first positive C plate 20b are laminated, for example, via an adhesive layer not shown. The first phase difference member 20 is arranged so that the angle between the absorption axis of the polarizing member 10 and the slow axis of the first λ / 4 member 20a is preferably 40° to 50°, more preferably 42° to 48°, for example, about 45°.
[0059] <Polarizing materials> The polarizing member 10 is typically an absorptive polarizing member including a resin film (sometimes referred to as an absorptive polarizing film) containing a dichroic material, and may further include a protective layer on one or both sides thereof as necessary. The protective layer is typically attached to the absorptive polarizing film via any suitable adhesive layer. A typical example of the adhesive forming the adhesive layer is an ultraviolet-curing adhesive.
[0060] The crossed transmittance (Tc) of the polarizing member (absorptive polarizing film) is preferably 0.5% or less, more preferably 0.1% or less, and even more preferably 0.05% or less. The single transmittance (Ts) of the polarizing member (absorptive polarizing film) is, for example, 41.0% to 45.0%, and preferably 42.0% or more. The degree of polarization (P) of the polarizing member (absorptive polarizing film) is, for example, 99.0% to 99.997%, and preferably 99.9% or more.
[0061] The crossed transmittance, single transmittance and degree of polarization can be measured, for example, using an ultraviolet-visible spectrophotometer. The degree of polarization P can be calculated from the obtained Tp and Tc by measuring the single transmittance Ts, parallel transmittance Tp and crossed transmittance Tc using an ultraviolet-visible spectrophotometer, using the following formula. Note that Ts, Tp and Tc are Y values measured using a 2-degree visual field (C light source) according to JIS Z8701 and corrected for visibility. Polarization degree P(%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0062] The thickness of the absorptive polarizing film is, for example, 1 μm or more and 20 μm or less, optionally 2 μm or more and 15 μm or less, optionally 12 μm or less, optionally 10 μm or less, optionally 8 μm or less, or optionally 5 μm or less.
[0063] The absorptive polarizing film may be prepared from a single layer of resin film, or may be prepared using a laminate of two or more layers.
[0064] When preparing from a single-layer resin film, for example, an absorptive polarizing film can be obtained by subjecting a hydrophilic polymer film such as a polyvinyl alcohol (PVA)-based film, a partially formalized PVA-based film, or an ethylene-vinyl acetate copolymer-based partially saponified film to a dyeing treatment with a dichroic substance such as iodine or a dichroic dye, a stretching treatment, etc. Among them, an absorptive polarizing film obtained by dyeing a PVA-based film with iodine and uniaxially stretching it is preferable.
[0065] The dyeing with iodine is carried out, for example, by immersing the PVA film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment or while the dyeing is being carried out. Alternatively, the stretching may be followed by dyeing. If necessary, the PVA film is subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like.
[0066] Examples of the laminate produced using the laminate of two or more layers include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The absorptive polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced, for example, by coating a PVA-based resin solution on the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into an absorptive polarizing film. In this embodiment, preferably, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction, thereby shrinking the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of PVA, and to achieve high optical properties. At the same time, by increasing the orientation of PVA in advance, problems such as a decrease in the orientation or dissolution of PVA when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of polyvinyl alcohol molecules and the decrease in the orientation can be suppressed compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of the absorptive polarizing film obtained through treatment steps in which the laminate is immersed in a liquid, such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through drying shrinkage treatment.The obtained laminate of the resin substrate / absorptive polarizing film may be used as it is (i.e., the resin substrate may also serve as the protective layer of the absorptive polarizing film), or an arbitrary appropriate protective layer according to the purpose may be laminated on the peeled surface of the resin substrate peeled from the laminate of the resin substrate / absorptive polarizing film or on the surface opposite to the peeled surface and used. Details of such a method for manufacturing an absorptive polarizing film are described, for example, in Japanese Patent Application Laid-Open No. 2012-73580 and Japanese Patent No. 6470455. The entire descriptions of these publications are incorporated herein by reference.
[0067] The protective layer can be formed of any appropriate resin film that can be used as the protective layer of the absorptive polarizing film. Specific examples of the resin that is the main component of the resin film include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based resins, polyvinyl alcohol-based resins, polycarbonate-based resins, polyamide-based resins, polyimide-based resins, polyethersulfone-based resins, polysulfone-based resins, polystyrene-based resins, cycloolefin-based resins such as polynorbornene, polyolefin-based resins, (meth)acrylic-based resins, acetate-based resins, and the like.
[0068] The thickness of the protective layer is typically 100 μm or less, for example, 5 μm to 80 μm, preferably 10 μm to 50 μm, and more preferably 15 μm to 35 μm.
[0069] <First λ / 4 member> The in-plane retardation Re(550) and the dispersion wavelength characteristics of the first λ / 4 member 20a are as described in Item A.
[0070] The first λ / 4 member preferably exhibits a refractive index characteristic relationship of nx > ny ≧ nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny < nz may occur. The Nz coefficient of the first λ / 4 member is preferably 0.9 to 3, more preferably 0.9 to 2.5, still more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.
[0071] The first λ / 4 member is made of any appropriate material that can satisfy the above characteristics. The first λ / 4 member can be, for example, a stretched resin film or an oriented and solidified layer of a liquid crystal compound.
[0072] Examples of the resin contained in the resin film include polycarbonate-based resins, polyester carbonate-based resins, polyester-based resins, polyvinyl acetal-based resins, polyarylate-based resins, cyclic olefin-based resins, cellulose-based resins, polyvinyl alcohol-based resins, polyamide-based resins, polyimide-based resins, polyether-based resins, polystyrene-based resins, and acrylic-based resins. These resins may be used alone or in combination. Examples of methods for combining include blending and copolymerization. When the first λ / 4 member exhibits reverse dispersion wavelength characteristics, a resin film containing a polycarbonate-based resin or a polyester carbonate-based resin (hereinafter, sometimes simply referred to as a polycarbonate-based resin) may be suitably used.
[0073] Any suitable polycarbonate-based resin can be used as the polycarbonate-based resin. For example, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from at least one dihydroxy compound selected from the group consisting of alicyclic diol, alicyclic dimethanol, di-, tri- or polyethylene glycol, and alkylene glycol or spiro glycol. Preferably, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, a structural unit derived from an alicyclic dimethanol and / or a structural unit derived from a di-, tri- or polyethylene glycol; more preferably, it contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from a di-, tri- or polyethylene glycol. The polycarbonate-based resin may contain a structural unit derived from another dihydroxy compound as necessary. Details of polycarbonate-based resins that can be suitably used for the first λ / 4 member and methods for forming the first λ / 4 member are described, for example, in JP 2014-10291 A, JP 2014-26266 A, JP 2015-212816 A, JP 2015-212817 A, and JP 2015-212818 A, and the descriptions in these publications are incorporated herein by reference.
[0074] The thickness of the first λ / 4 member made of a stretched resin film is, for example, 10 μm to 100 μm, preferably 10 μm to 70 μm, and more preferably 20 μm to 60 μm.
[0075] The above-mentioned liquid crystal compound alignment solidified layer is a layer in which the liquid crystal compound is aligned in a predetermined direction within the layer, and the alignment state is fixed. The "alignment solidified layer" is a concept that includes an alignment solidified layer obtained by hardening a liquid crystal monomer as described later. In the first λ / 4 member, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the first λ / 4 member (homogeneous alignment). Examples of rod-shaped liquid crystal compounds include liquid crystal polymers and liquid crystal monomers. The liquid crystal compound is preferably polymerizable. If the liquid crystal compound is polymerizable, the alignment state of the liquid crystal compound can be fixed by aligning the liquid crystal compound and then polymerizing it.
[0076] The alignment solidified layer of the liquid crystal compound (liquid crystal alignment solidified layer) can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. Any appropriate alignment treatment can be adopted as the alignment treatment. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any appropriate conditions can be adopted depending on the purpose.
[0077] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.
[0078] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is polymerizable or crosslinkable, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or crosslinking treatment.
[0079] As the liquid crystal compound, any suitable liquid crystal polymer and / or liquid crystal monomer is used. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination. Specific examples of the liquid crystal compound and the method for producing the liquid crystal alignment solidified layer are described in, for example, JP 2006-163343 A, JP 2006-178389 A, and WO 2018 / 123551 A. The descriptions in these publications are incorporated herein by reference.
[0080] The thickness of the first λ / 4 member constituted by the liquid crystal alignment solidified layer is, for example, 1 μm to 10 μm, preferably 1 μm to 8 μm, more preferably 1 μm to 6 μm, and further preferably 1 μm to 4 μm.
[0081] <First positive C plate> The thickness direction retardation Rth(550) of the first positive C plate 20b is preferably -20 nm to -200 nm, more preferably -30 nm to -180 nm, further preferably -40 nm to -160 nm, and particularly preferably -50 nm to -140 nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. The in-plane retardation Re(550) of the first positive C plate is, for example, less than 10 nm.
[0082] The first positive C plate may be formed of any appropriate material. The first positive C plate is preferably composed of a film containing a liquid crystal material fixed in homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of such liquid crystal compounds and methods for forming a positive C plate include the liquid crystal compounds and methods for forming the retardation layer described in
[0020] to
[0028] of JP-A-2002-333642. In this case, the thickness of the first positive C plate is preferably 0.5 μm to 5 μm.
[0083] <First protective member> The first protective member 41 typically includes a substrate. The substrate may be made of any appropriate film. Examples of materials that are the main components of the film that constitutes the substrate include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, cycloolefin-based such as polynorbornene, polyolefin-based, (meth)acrylic-based, acetate-based, and other resins. The thickness of the substrate is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and further preferably 15 μm to 35 μm.
[0084] The first protective member preferably has a substrate and a surface treatment layer formed on the substrate. The first protective member having the surface treatment layer may be disposed so that the surface treatment layer is located on the front side. Specifically, the surface treatment layer may be located on the outermost surface of the optical film 50a. The surface treatment layer may have any appropriate function. Examples of the surface treatment layer include a hard coat layer, an anti-reflection layer, an anti-sticking layer, and an anti-glare layer. The first protective member may have two or more surface treatment layers.
[0085] The antireflection layer is provided to prevent reflection of external light and the like. Examples of the antireflection layer include a fluororesin layer, a resin layer containing nanoparticles (typically hollow nanoparticles, e.g., hollow nanosilica particles), and an antireflection layer having a nanostructure (e.g., a moth-eye structure). The thickness of the antireflection layer is preferably 0.05 μm to 1 μm. Examples of methods for forming the resin layer include a sol-gel method, a heat curing method using an isocyanate, and an ionizing radiation curing method (typically a photocuring method) using a crosslinkable monomer (e.g., a polyfunctional acrylate) and a photopolymerization initiator. In one embodiment, the antireflection layer is provided on the outermost surface of the first protective member. According to an embodiment in which the antireflection layer is provided on the outermost surface of the first protective member, an excellent antireflection effect can be obtained in a display system in which a space is formed between the half mirror 18 and the first phase difference member 20.
[0086] The hard coat layer preferably has sufficient surface hardness, excellent mechanical strength, and excellent light transmittance. The hard coat layer may be formed from any suitable resin. The hard coat layer is typically formed from an ultraviolet curing resin. Examples of the ultraviolet curing resin include polyester, acrylic, urethane, amide, silicone, and epoxy resins. The thickness of the hard coat layer is, for example, 0.5 μm or more, preferably 1 μm or more, for example, 20 μm or less, preferably 15 μm or less.
[0087] <Adhesive layer> The adhesive layer 31 may be made of any suitable adhesive. Specific examples include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and compounding ratio of monomers forming the base resin of the adhesive, as well as the compounding amount of the crosslinking agent, reaction temperature, reaction time, and the like, an adhesive having desired properties according to the purpose can be prepared. The base resin of the adhesive may be used alone or in combination of two or more kinds. An acrylic resin is preferably used as the base resin. Specifically, the adhesive layer is preferably made of an acrylic adhesive.
[0088] The thickness of the pressure-sensitive adhesive layer is typically 1 μm or more, preferably 5 μm or more, more preferably 12 μm or more, and typically 60 μm or less, preferably 30 μm or less, more preferably 23 μm or less.
[0089] <Release liner> The release liner 36 is formed of any appropriate resin film. Specific examples of materials that are the main components of the resin film include polyethylene terephthalate (PET), polyethylene, and polypropylene. The resin film materials can be used alone or in combination. The release liner may be transparent (e.g., haze of 5% or less, e.g., 3% or less) or not transparent. When inspecting the optical film with the surface protection film with the release liner attached, it is preferable that the release liner is transparent.
[0090] A release treatment layer may be provided on the surface of the release liner 36 that comes into contact with the pressure-sensitive adhesive layer 31. Examples of release treatment agents that form the release treatment layer include silicone-based release treatment agents, fluorine-based release treatment agents, and long-chain alkyl acrylate-based release treatment agents. The release treatment agents can be used alone or in combination. The thickness of the release treatment layer is typically 50 nm or more and 400 nm or less.
[0091] The thickness of the release liner is typically 5 μm or more, preferably 20 μm or more, and typically 60 μm or less, preferably 45 μm or less. When a release treatment layer is applied, the thickness of the release liner includes the thickness of the release treatment layer.
[0092] FIG. 5 is a schematic cross-sectional view for explaining an example of the configuration of an optical film applicable to an embodiment of the present invention. The optical film 50b includes a pressure-sensitive adhesive layer 32, a second phase difference member 22, and a second protective member 42 in this order. The second phase difference member 22 and the second protective member 42 are laminated via an adhesive layer 35. The adhesive layer 35 is typically an adhesive layer or a pressure-sensitive adhesive layer, and is preferably a pressure-sensitive adhesive layer. The thickness of the adhesive layer is, for example, 0.05 μm to 30 μm. The surface of the pressure-sensitive adhesive layer 32 is protected by a release liner 37 until it is used. With respect to the optical film 50b, a surface protection film layer is disposed on the surface on the second protective member 42 side.
[0093] The optical film 50b can be suitably used in the display system 2 illustrated in FIG. 1. Specifically, by peeling off the release liner 37 from the optical film 50b and integrating it with the first lens portion 16 via the exposed adhesive layer 32, a display system can be manufactured in which the second retardation member 22 is integrally provided on the first lens portion 16.
[0094] In the example shown in FIG. 5, the second retardation member 22 includes, in addition to the second λ / 4 member 22a, a member (so-called positive C-plate) 22b that can exhibit a refractive index characteristic of nz > nx = ny. The second retardation member 22 has a laminated structure of the second λ / 4 member 22a and the second positive C-plate 22b. Different from the illustrated example, the second positive C-plate 22b may be located closer to the second protective member 42 side than the second λ / 4 member 22a, and the second positive C-plate 22b may be omitted. The second λ / 4 member 22a and the second positive C-plate 22b are laminated via, for example, an adhesive layer (not shown).
[0095] <Second λ / 4 member> The in-plane retardation Re(550) and the dispersion wavelength characteristics of the second λ / 4 member 22a are as described in item A.
[0096] The second λ / 4 member preferably exhibits a refractive index characteristic of nx > ny ≥ nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny < nz may occur. The Nz coefficient of the second λ / 4 member is preferably 0.9 to 3, more preferably 0.9 to 2.5, still more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.
[0097] The second λ / 4 member is formed of any appropriate material that can satisfy the above characteristics. The second λ / 4 member can be, for example, a stretched resin film or an oriented and solidified layer of a liquid crystal compound. The same explanation as for the first λ / 4 member can be applied to the second λ / 4 member composed of a stretched resin film or an oriented and solidified layer of a liquid crystal compound. The first λ / 4 member and the second λ / 4 member may have the same configuration (e.g., forming material, thickness, optical properties, etc.) or different configurations.
[0098] <Second positive C plate> The thickness direction retardation Rth(550) of the second positive C plate 22b is preferably -20 nm to -200 nm, more preferably -30 nm to -180 nm, further preferably -40 nm to -160 nm, and particularly preferably -50 nm to -140 nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. The in-plane retardation Re(550) of the second positive C plate is, for example, less than 10 nm.
[0099] The second positive C plate is formed of any appropriate material that can satisfy the above characteristics. The same explanation as for the first positive C plate can be applied to the constituent material of the second positive C plate. The first positive C plate and the second positive C plate may have the same configuration (e.g., forming material, thickness, optical properties, etc.) or may have different configurations.
[0100] <Second protective member> The second protective member 42 typically includes a substrate, and preferably has a substrate and a surface treatment layer formed on the substrate. In this case, the surface treatment layer may be located on the outermost surface of the optical film 50b. The same explanation as for the first protective member can be applied to the details of the substrate and the surface treatment layer. According to an embodiment in which an antireflection layer is provided on the outermost surface of the second protective member 42 as the surface treatment layer, an excellent antireflection effect can be obtained in a display system in which the second phase difference member 22 is integrated with the first lens portion 16, the reflective portion 14 is integrated with the second lens portion 24, and a space is formed between them.
[0101] The same explanations as for the pressure-sensitive adhesive layer 31 and release liner 36 used in the optical film 50a can be applied to the pressure-sensitive adhesive layer 32 and release liner 37 used in the optical film 50b.
[0102] <Method of manufacturing optical film with surface protective film> The optical film with a surface protective film can be produced by any suitable method. For example, two or more PFs are laminated to produce a surface protective film layer, and the surface protective film layer is laminated to an optical film, thereby producing an optical film with a surface protective film. For example, two or more PFs are laminated in sequence to one side of an optical film, thereby producing an optical film with a surface protective film. Alternatively, the optical film with a surface protective film can be obtained by providing a surface protective film layer on the outermost member (e.g., a protective member) of the optical film, and laminating the member with the surface protective film layer with another member to produce an optical film.
[0103] C. Optical film inspection method A method for inspecting an optical film according to an embodiment of the present invention includes: Peeling off the outermost layer PF from the optical film with a surface protective film described in item B to obtain an optical film protected by at least the innermost layer PF; and subjecting the optical film protected by at least the innermost layer PF to a defect inspection; Includes. As described above, according to the optical film with surface protective film described in Section B, peeling of the inner PF (e.g., the innermost PF or intermediate PF) can be suitably suppressed when peeling off the outer PF (e.g., the intermediate PF or the outermost PF). Therefore, by peeling off the outer PF from the optical film with surface protective film described in Section B, an optical film protected by at least the innermost PF can be suitably obtained. Here, the surface of the inner PF exposed by peeling off the outer PF is prevented from adhesion of scratches, dirt, etc. Therefore, by peeling off the outer PF immediately before inspection, an optical film protected by a clean PF can be subjected to defect inspection, and erroneous detection of defects caused by scratches and dirt on the PF surface can be suppressed.
[0104] The defect inspection can be performed by any suitable defect inspection device. As the defect inspection device, a known defect inspection device can be used, and preferably an automatic optical inspection (AOI) device is used. Examples of documents in which the defect inspection device is described include International Publication No. 2011 / 148790, JP 2003-344302 A, JP 2011-226957 A, JP 2016-70856 A, and JP 2021-135219 A. The defect inspection may further include visual inspection as necessary. EXAMPLES
[0105] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The thicknesses are values measured by the following measuring method. <Thickness> The thickness was measured using a digital micrometer (manufactured by Anritsu Corporation, product name "KC-351C"). <Total light transmittance and haze> For the surface protection film, the release liner was peeled off from the adhesive layer, and light was irradiated from the substrate side using a haze meter ("HZ-V3" manufactured by Suga Test Instruments Co., Ltd.), and the haze was calculated according to JIS-K-7136 by the formula: haze (%) = (Td / Tt) x 100 (Td: diffuse transmittance, Tt: total light transmittance). The total light transmittance was measured according to JIS-K-7316. <Water contact angle> The water contact angle of the anti-reflection layer side surface of the optical film was measured. Specifically, the measurement was performed by the sessile drop method using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., product name "DMo-501 type", control box "DMC-2", control and analysis software "FAMAS (version 5.0.30)") in an environment of 23°C and 50% RH. The amount of distilled water dropped was 2 μL, and the contact angle was calculated by the θ / 2 method from the image taken 5 seconds after the drop.
[0106] [Production Example 1-1: Preparation of PF1] <Acrylic polymer 1> In a reaction vessel equipped with a thermometer, a stirrer, a cooler, and a nitrogen gas inlet tube, 96.2 parts by weight of 2-ethylhexyl acrylate (2EHA), 3.8 parts by weight of 2-hydroxyethyl acrylate (HEA), and 0.2 parts by weight of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator were charged together with 150 parts by weight of ethyl acetate, and nitrogen gas was introduced while gently stirring at 23°C to perform nitrogen substitution. Thereafter, the liquid temperature was kept at around 65°C and a polymerization reaction was carried out for 6 hours, producing a solution of acrylic polymer 1 (concentration 40% by weight). The weight average molecular weight of acrylic polymer 1 was 540,000. Furthermore, the Tg of acrylic polymer 1 was calculated according to the FOX formula as (-70°C x 0.962) + (-15°C x 0.038) = (-67.34°C) + (-0.57°C) = -67.91°C. <Adhesive composition 1> 5 parts by weight of an isocyanurate of hexamethylene diisocyanate ("Coronate HX" manufactured by Tosoh Corporation) was added as a crosslinking agent to 100 parts by weight of the solid content of the acrylic polymer 1 solution. The solution was diluted with toluene so that the total solid content was 20% by weight, and 3 parts by weight (solid content 0.03 parts by weight) of dibutyltin dilaurate (1% by weight solution in ethyl acetate) was added as a crosslinking catalyst and stirred, followed by stirring with a disperser to produce adhesive composition 1. <pf1> The pressure-sensitive adhesive composition 1 was applied to the surface (corona-treated surface) of a substrate (cyclic olefin film, Zeon Corporation, product number ZF-16, thickness 50 μm) and then dried to form a pressure-sensitive adhesive layer (thickness 10 μm). Next, a release liner (Toyobo Co., Ltd., product number TG704) was attached to the surface of the pressure-sensitive adhesive layer opposite the substrate. This resulted in PF1 (thickness 60 μm) with a haze of 1.0% or less and a total light transmittance of 90% or more.
[0107] [Production Example 1-2: Preparation of PF2] <Acrylic polymer 2> In a reaction vessel equipped with a thermometer, a stirrer, a cooler, and a nitrogen gas inlet tube, 100 parts by weight of 2-ethylhexyl acrylate (2EHA) and 4 parts by weight of hexyl acrylate as monomer components, and 0.2 parts by weight of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator were charged together with 150 parts by weight of ethyl acetate, and nitrogen gas was introduced while gently stirring at 23°C to perform nitrogen substitution. Thereafter, the liquid temperature was kept at around 65°C and a polymerization reaction was carried out for 6 hours, to prepare a solution of acrylic polymer 2 (concentration 40% by weight). The weight average molecular weight of acrylic polymer 2 was 530,000. <Adhesive composition 2> Ethyl acetate was added to the solution of acrylic polymer 2 to dilute it to a concentration of 20% by weight. 4 parts by weight of an isocyanurate of hexamethylene diisocyanate ("Coronate HX" manufactured by Tosoh Corporation) as a crosslinking agent and 0.2 parts by weight of a surfactant ("Aqualon HS-10" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were added to 500 parts by weight of this solution (solid content 100 parts by weight) and stirred to prepare adhesive composition 2. <pf2> The pressure-sensitive adhesive composition 2 was applied to the surface (corona-treated surface) of a substrate (PET film, manufactured by Mitsubishi Chemical Corporation, product number T100C38, thickness 38 μm) and then dried to form a pressure-sensitive adhesive layer (thickness 20 μm). Next, a release liner (manufactured by Toyobo Co., Ltd., product number TG704) was attached to the surface of the pressure-sensitive adhesive layer opposite to the substrate. This resulted in PF2 (thickness: 58 μm) having a haze of 3.0% or less and a total light transmittance of 90% or more.
[0108] [Production Example 1-3: Preparation of PF3] <Adhesive composition 3> To 100 parts by weight of the solid content of the acrylic polymer 1 solution obtained in Production Example 1-1, 4 parts by weight of an isocyanurate of hexamethylene diisocyanate ("Coronate HX" manufactured by Tosoh Corporation) was added as a crosslinking agent. The mixture was diluted with toluene so that the total solid content was 20% by weight, and 3 parts by weight (solid content 0.03 parts by weight) of dibutyltin dilaurate (1% by weight toluene solution) was added as a crosslinking catalyst and stirred, followed by stirring with a disperser to produce adhesive composition 3. <pf3> The pressure-sensitive adhesive composition 3 was applied to the surface (corona-treated surface) of a substrate (PET film, manufactured by Mitsubishi Chemical Corporation, product number T100C38, thickness 38 μm) and then dried to form a pressure-sensitive adhesive layer (thickness 10 μm). Next, a release liner (manufactured by Toyobo Co., Ltd., product number TG704) was attached to the surface of the pressure-sensitive adhesive layer opposite to the substrate. This resulted in PF3 (thickness 48 μm) with a haze of 3.0% or less and a total light transmittance of 90% or more.
[0109] [Production Example 1-4: Preparation of PF4] <Adhesive composition 4> To 100 parts by weight of the solid content of the acrylic polymer 1 solution obtained in Production Example 1-1, 4.0 parts by weight of Takenate D-101E (manufactured by Mitsui Chemicals, Inc.) was added as a crosslinking agent in terms of solid content. The mixture was diluted with toluene so that the total solid content became 29% by weight, and stirred with a disperser to produce adhesive composition 4. <pf4> The pressure-sensitive adhesive composition 4 was applied to the surface (corona-treated surface) of a substrate (PET film, manufactured by Mitsubishi Chemical Corporation, product number T100C38, thickness 38 μm) and then dried to form a pressure-sensitive adhesive layer (thickness 23 μm). Next, a release liner (manufactured by Toyobo Co., Ltd., product number TG704) was attached to the surface of the pressure-sensitive adhesive layer opposite to the substrate. This resulted in PF4 (thickness 61 μm) with a haze of 3.0% or less and a total light transmittance of 90% or more.
[0110] The peel strength of PF1 to PF4 was measured as follows. The measurements were performed under conditions of 23° C. and 50% RH. The results are shown in Table 1. (1) The adhesive layer surface of the surface protection film A to be measured was roll-pressed to the adherend B at a pressure of 0.25 MPa and a feed speed of 0.3 m / min, and left for 30 minutes to prepare a measurement sample C (size: length 150 mm, width 25 mm). (2) Measurement sample C was fixed onto a metal or glass plate using double-sided tape (manufactured by Nitto Denko Corporation, product name "No. 5000NS") with adherend B facing down. (3) As shown in Figures 6A and 6B, an adhesive tape T (manufactured by Nitto Denko Corporation, product name "No. 31B", size: length 50 mm, width 20 mm) was attached to surface protection film A of measurement sample C so that one end was exposed and the longitudinal directions were parallel, and the peel force was measured when the one end was grasped and pulled in the direction of the arrow (peel angle 180°, peel speed 300 mm / min).
[0111] [Table 1]
[0112] [Production Example 2: Preparation of Polarizing Film 1] A long roll of polyvinyl alcohol (PVA) resin film (manufactured by Kuraray Co., Ltd., product name "PE3000") with a thickness of 30 μm was uniaxially stretched in the longitudinal direction to 5.9 times its original size using a roll stretching machine, while simultaneously undergoing swelling, dyeing, crosslinking, and washing processes, and finally a drying process to produce an absorptive polarizing film with a thickness of 12 μm. Specifically, the film was stretched 2.2 times during the swelling treatment in pure water at 20°C. Next, the film was stretched 1.4 times during the dyeing treatment in an aqueous solution at 30°C in which the weight ratio of iodine to potassium iodide was 1:7, and the iodine concentration was adjusted so that the single transmittance of the resulting absorptive polarizing film was 45.0%. Furthermore, a two-stage crosslinking treatment was adopted, and the film was stretched 1.2 times during the first stage crosslinking treatment in an aqueous solution at 40°C in which boric acid and potassium iodide were dissolved. The boric acid content of the aqueous solution in the first stage crosslinking treatment was 5.0% by weight, and the potassium iodide content was 3.0% by weight. The film was stretched 1.6 times during the second stage crosslinking treatment in an aqueous solution at 65°C in which boric acid and potassium iodide were dissolved. The boric acid content of the aqueous solution in the second stage crosslinking treatment was 4.3% by weight, and the potassium iodide content was 5.0% by weight. The cleaning treatment was performed with an aqueous potassium iodide solution at 20° C. The aqueous solution used for the cleaning treatment had a potassium iodide content of 2.6% by weight. Finally, the film was dried at 70° C. for 5 minutes to obtain an absorptive polarizing film. A triacetyl cellulose (TAC) resin film with a hard coat (HC) layer (TAC thickness: 25 μm, HC thickness: 7 μm) was attached to one side of the obtained absorptive polarizing film, and a cycloolefin resin film (thickness: 13 μm) was attached to the other side as a protective layer. Specifically, the curable adhesive was applied so that the total thickness was about 1 μm, and the two were laminated using a roller. Then, UV light was irradiated from the TAC film side to cure the adhesive. As a result, polarizing film 1 having a structure of [TAC film (protective layer) / absorptive polarizing film / COP film (protective layer)] was obtained.
[0113] [Manufacturing Example 3: Preparation of protective member 1] (Preparation of Hard Coat Layer Forming Material) A hard coat layer forming material was prepared by mixing 50 parts of a urethane acrylic oligomer (manufactured by Shin-Nakamura Chemical Co., Ltd., "NK Oligo UA-53H"), 30 parts of a multifunctional acrylate mainly composed of pentaerythritol triacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name "Viscoat #300"), 20 parts of 4-hydroxybutyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.), 1 part of a leveling agent (manufactured by DIC Corporation, "GRANDIC PC4100") and 3 parts of a photopolymerization initiator (manufactured by Ciba Japan, "Irgacure 907") and diluting with methyl isobutyl ketone to a solids concentration of 50%.
[0114] (Preparation of Coating Solution for Forming High Refractive Index Layer) 100 parts by weight of a multifunctional acrylate (manufactured by Arakawa Chemical Industries, Ltd., product name "Opstar KZ6728", solid content 20% by weight), 3 parts by weight of a leveling agent (manufactured by DIC Corporation, "GRANDIC PC4100"), and 3 parts by weight of a photopolymerization initiator (manufactured by BASF, product name "OMNIRAD907", solid content 100% by weight) were mixed. The mixture was diluted with butyl acetate as a diluting solvent to a solid content of 12% by weight, and stirred to prepare a coating liquid for forming a high refractive index layer.
[0115] (Preparation of Coating Solution for Forming Low Refractive Index Layer) 100 parts by weight of a polyfunctional acrylate mainly composed of pentaerythritol triacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "Viscoat #300", solid content 100% by weight), 150 parts by weight of hollow nanosilica particles (manufactured by JGC Catalysts and Chemicals Co., Ltd., trade name "Surulia 5320", solid content 20% by weight, weight average particle diameter 75 nm), 50 parts by weight of solid nanosilica particles (manufactured by Nissan Chemical Industries, Ltd., trade name "MEK-2140Z-AC", solid content 30% by weight, weight average particle diameter 10 nm), 12 parts by weight of a fluorine-containing additive (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KY-1203", solid content 20% by weight), and 3 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907", solid content 100% by weight) were mixed. To the mixture was added a mixed solvent of TBA (tertiary butyl alcohol), MIBK (methyl isobutyl ketone) and PMA (propylene glycol monomethyl ether acetate) in a weight ratio of 60:25:15 as a dilution solvent until the total solids content was 4% by weight, and the mixture was stirred to prepare a coating liquid for forming a low refractive index layer.
[0116] The above hard coat layer forming material was applied to an acrylic film (thickness 40 μm) having a lactone ring structure as a substrate, and heated at 90° C. for 1 minute. After heating, the coating layer was irradiated with a high-pressure mercury lamp with an integrated light quantity of 300 mJ / cm 2 2 The coating layer was cured by irradiation with ultraviolet light of 1000 .mu.m to prepare an acrylic film (thickness 44 .mu.m) on which a hard coat layer with a thickness of 4 .mu.m was formed. Next, the coating liquid for forming the high refractive index layer was applied onto the hard coat layer using a wire bar, and the applied coating liquid was heated at 80° C. for 1 minute and dried to form a coating film. The dried coating film was then irradiated with a high-pressure mercury lamp with an integrated light quantity of 300 mJ / cm 2 . 2 The coating was cured by irradiating it with ultraviolet light of 1,000 ohms to form a high refractive index layer having a thickness of 140 nm. Next, the above-mentioned low refractive index layer forming coating liquid was applied onto the high refractive index layer with a wire bar, and the applied coating liquid was heated at 80°C for 1 minute and dried to form a coating film. The dried coating film was irradiated with a high pressure mercury lamp with an integrated light amount of 300 mJ / cm2. 2 The coating was cured by irradiating it with ultraviolet light of 100 .ANG. to form a low refractive index layer having a thickness of 105 nm. As a result, an antireflection layer composed of a high refractive index layer and a low refractive index layer was formed on the hard coat layer. As a result, a protective member 1 having a structure of [antireflection layer / hard coat layer / substrate] was obtained. The water contact angle of the surface on the antireflection layer side was 110°.
[0117] [Production Example 4: Preparation of Optical Film 1] The substrate surface of protective member 1 was bonded via an acrylic pressure-sensitive adhesive layer (thickness 25 μm) to the TAC film surface of polarizing film 1 obtained in Production Example 2. In addition, an acrylic pressure-sensitive adhesive layer (thickness 25 μm) formed on a release liner was bonded to the COP film surface of polarizing film 1 to produce optical film 1 having a configuration of [release liner / pressure-sensitive adhesive layer / polarizing film 1 / protective member 1].
[0118] [Example 1] The adhesive layer surface of PF2 obtained in Production Example 1-2 was bonded to the substrate surface of PF1 obtained in Production Example 1-1 to form a surface protective film layer 1 composed of PF1 as the innermost layer PF and PF2 as the outermost layer PF. The pressure-sensitive adhesive layer surface of the surface protection film layer 1 (more specifically, the pressure-sensitive adhesive layer surface of PF1) was attached to the protective member 1 surface of the optical film 1 to obtain an optical film 1 with a surface protection film.
[0119] [Example 2] The adhesive layer surface of PF3 obtained in Production Example 1-3 was bonded to the substrate surface of PF1 obtained in Production Example 1-1 to form a surface protective film layer 2 composed of PF1 as the innermost layer PF and PF3 as the outermost layer PF. The pressure-sensitive adhesive layer surface of the surface protective film layer 2 (more specifically, the pressure-sensitive adhesive layer surface of PF1) was attached to the protective member 1 surface of the optical film 1 to obtain an optical film 2 with a surface protective film.
[0120] [Comparative Example 1] The adhesive layer surface of PF4 obtained in Production Example 1-4 was bonded to the substrate surface of PF1 obtained in Production Example 1-1 to form a surface protective film layer 3 composed of PF1 as the innermost layer PF and PF4 as the outermost layer PF. The pressure-sensitive adhesive layer surface of the surface protective film layer 3 (more specifically, the pressure-sensitive adhesive layer surface of PF1) was attached to the protective member 1 surface of the optical film 1 to obtain an optical film C1 with a surface protective film.
[0121] <Peel test> The optical films with surface protective films obtained in the examples and comparative examples were cut into rectangles (size: length 32 mm, width 28 mm) and the four corners were chamfered (chamfer dimension: 2 mm) to prepare measurement samples. (1) Peeling starting from the short side As shown in FIG. 7A, a 50 mm long, 20 mm wide adhesive tape T (manufactured by Nitto Denko Corporation, product name "No. 31B") was attached to the surface of the surface protection film layer 60 of the measurement sample 100 so that the length direction was parallel and one end was exposed. The one end was gripped and pulled at a peel speed of 300 mm / min and a peel angle of 90° or 180° to peel off the outermost layer PF. For each peel angle, a test was performed with an N number of 25. The number of times (NG number) that the innermost layer PF peeled off simultaneously with the outermost layer PF is shown in Table 2. (2) Peeling starting from a corner As shown in FIG. 7B, a 50 mm long, 20 mm wide adhesive tape T (manufactured by Nitto Denko Corporation, product name "No. 31B") was attached to the surface of the surface protection film layer 60 of the measurement sample 100 so that the length direction was at an angle of 45° with the length direction of the measurement sample 100 and one end was exposed. The one end was gripped and pulled at a peel speed of 300 mm / min and a peel angle of 90° or 180° to peel off the outermost layer PF. For each peel angle, a test was performed with an N number of 25. The number of times (NG number) that the innermost layer PF peeled off simultaneously with the outermost layer PF is shown in Table 2.
[0122] [Table 2]
[0123] As shown in Table 2, in the optical films with surface protective films of the embodiments in which P2 was 3.5 times or less than P1, simultaneous peeling of the inner PF was suppressed when peeling the outermost PF, regardless of the peel starting point and peel angle. [Industrial Applicability]
[0124] The optical film with a surface protective film according to the embodiment of the present invention can be suitably used in the manufacture of display systems such as VR goggles, for example. [Explanation of symbols]
[0125] 2 display system, 12 display element, 14 reflecting portion, 16 first lens portion, 18 half mirror, 20 first phase difference member, 22 second phase difference member, 24 second lens portion, 50 optical film, 60 surface protection film layer, 62 innermost surface protection film, 64 outermost surface protection film, 66 intermediate surface protection film, 100 optical film with surface protection film
Claims
1. An optical film; and a surface protective film layer disposed on one side of the optical film, The surface protection film layer includes two or more surface protection films each having a substrate and a pressure-sensitive adhesive layer, An optical film with a surface protective film, in which a peeling force P1 of an innermost surface protective film arranged closest to the optical film in the surface protective film layer, and a peeling force P2 of an outermost surface protective film arranged on the outermost side of the surface protective film layer, to an adjacent surface protective film, satisfy the relationship of the following formula (1): P2≦3.5×P1 (1).
2. the surface protective film layer is composed of the innermost surface protective film, an intermediate surface protective film, and the outermost surface protective film, 2. The optical film with a surface protective film according to claim 1, wherein a peeling force P2 of the outermost surface protective film to the intermediate surface protective film and a peeling force P3 of the intermediate surface protective film to the innermost surface protective film satisfy the relationship of the following formulas (2) and (3): P2≦2.5×P3 (2), P3≦2×P1 (3).
3. 2 . The optical film with a surface protective film according to claim 1 , wherein a ratio (T1 / T2) of a thickness T1 of the innermost surface protective film to a thickness T2 of the outermost surface protective film is 1.03 or more.
4. 2 . The optical film with a surface protective film according to claim 1 , wherein the bending strength of the substrate of the innermost surface protective film at 23° C. is equal to or greater than the bending strength of the substrate of the outermost surface protective film at 23° C.
5. The optical film with a surface protective film according to claim 1 , wherein the surface of the optical film on the side of the surface protective film layer is an antireflection layer.
6. 2 . The optical film with a surface protective film according to claim 1 , wherein the surface of the optical film on the side of the surface protective film layer has a water contact angle of 80° or more.
7. peeling off the outermost surface protective film from the optical film with a surface protective film according to any one of claims 1 to 6 to obtain the optical film protected by at least the innermost surface protective film; and subjecting the optical film protected by at least the innermost surface protective film to a defect inspection; A method for inspecting an optical film, comprising:
Citation Information
Patent Citations
Laminate for organic el displays and circular polarizing plate used therefor
JP2021103286A